2022
DOI: 10.1038/s41467-022-35352-9
|View full text |Cite
|
Sign up to set email alerts
|

Strain control of hybridization between dark and localized excitons in a 2D semiconductor

Abstract: Mechanical strain is a powerful tuning knob for excitons, Coulomb-bound electron–hole complexes dominating optical properties of two-dimensional semiconductors. While the strain response of bright free excitons is broadly understood, the behaviour of dark free excitons (long-lived excitations that generally do not couple to light due to spin and momentum conservation) or localized excitons related to defects remains mostly unexplored. Here, we study the strain behaviour of these fragile many-body states on pri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 70 publications
3
14
1
Order By: Relevance
“…the Supplementary material . The integrated intensity of the low-energy peak increases linearly with the excitation power, contrary to the saturating behaviour expected from defects 44 , 45 . In addition, we also observe a blue-shift of the peak with increasing excitation powers, similar to the behaviour of interlayer excitons, which blueshift due to dipole–dipole repulsion 46 .…”
Section: Resultscontrasting
confidence: 61%
“…the Supplementary material . The integrated intensity of the low-energy peak increases linearly with the excitation power, contrary to the saturating behaviour expected from defects 44 , 45 . In addition, we also observe a blue-shift of the peak with increasing excitation powers, similar to the behaviour of interlayer excitons, which blueshift due to dipole–dipole repulsion 46 .…”
Section: Resultscontrasting
confidence: 61%
“…[ 17–25 ] More recent work builds upon this idea and proposes that point defects, such as atomic vacancies, in addition to strain, are essential to form SPEs. [ 26–32 ] Under these conditions, it is hypothesized that SPEs originate from the hybridization of the strained dark exciton band and a valley symmetry‐breaking defect state. This model was recently supported in a study where the formation of SPEs was observed after applying both strain and electron beam (e − ‐beam) irradiation to WSe 2 .…”
Section: Introductionmentioning
confidence: 99%
“…12,13 With regard to optical properties, local strain application can induce exciton funneling, 14,15 efficient exciton to trion conversion 16 or the formation of a new hybrid state of dark and localized excitons. 17…”
Section: Introductionmentioning
confidence: 99%